RULE OF LAW AND ITS EFFECT ON CHINESE ECONOMIC DEVELOPMENT - Roziqin Roziqin (AL WASATH Jurnal Ilmu Hukum, 2021)
China's economic growth during the Covid-19 pandemic was impressive because it did not fell into recession. China's government has become a role model for facing Covid-19 outbreaks. China is now the world's wealthiest country, if we see its Gross Domestic Product from Purchasing Power Parity (GDP-PPP). China's position as the number one globally is faster than Jacques's prediction in 2009 that it will happen in 2050. For China, which does not implement liberal democracy, the writer hypothesizes that the reasonable choice to develop the economy is state-driven development through the rule of law. At present, the rule of law has become a daily conversation of the Chinese people. However, there are still many outsiders who doubt China has and applies the rule of law. It happens because China implements the rule of law with Chinese characteristics. This research will study the rule of law with Chinese characteristics, China's effort to implement the rule of law, and the rule of law on China's economy. This study uses a qualitative descriptive approach to explain the rule of law with Chinese characteristics. It will analyze the rule of law concept and its effect on China's economy. China applies the rule of law with Chinese characteristics based on Chinese traditions, which are heavily influenced by Confucius's teachings and prioritize obligations rather than rights. China has done many reforms action to implement the rule of law. The implementation of the rule of law in china makes China become a prosperous country now.